Blastomycosis presenting as solitary nodule: A rare presentation - Ashish Dhamija; Paschal D'Souza; Priti Salgia; Ashok Meherda; Rajkumar Kothiwala (Wolters Kluwer Medknow Publications, 2012)
Blastomycosis is a chronic granulomatous and suppurative mycosis, caused by Blastomyces dermatitidis, which in the great majority of cases presents as a primary pulmonary disease. Primary cutaneous blastomycosis is very rare. We present a 57-year-old female patient with a solitary, slowly progressive nodule over upper lip of 2½ months duration. Initially, differential diagnosis of cutaneous leishmaniasis, pyoderma and deep mycoses were entertained. Slit smear preparation was suspicious of deep mycotic infection which was subsequently confirmed by biopsy and culture.